use the laplace method to solve the equation
d2y/dx2+9y=9x y(0)=1 y'(0)=5
"\\text{The given differential equation can be written as }y''+9y-9x=0\\\\\\text{Next, we take the laplace transform of the differential equation}\\\\L(y'') =S^2L(y)-Sy(0)-y'(0)\\\\L(y')=SL(y)-y(0)\n\\\\L(y)=\\overline{y}\\\\\\implies S^2\\overline{y}-Sy(0)-y'(0)+9\\overline{y}=\\frac{9}{s^2}\n\\\\\\overline{y}(s^2+9)-s-5= \\frac{9}{s^2}\n\\\\\\overline{y}(s^2+9)= \\frac{9}{s^2}+s+5=\\frac{s^3+5s^2+9}{s^2(s^2+9)}-(1)\\\\\\text{Resolving (1) into partial fractions, where }\\\\\\frac{s^3+5s^2+9}{s^2(s^2+9)}=\\frac{A}{S}+\\frac{B}{S^2}+\\frac{CS+D}{S^2+9 } \\\\\\implies s^3+5s^2+9=AS(S^2+9)+B(S^2+9)+S^2(CS+D)\n\\\\\\text{Comparing co-efficients, we have that, A=0, B=1, C=1 and D=4} \\\\\\implies \\frac{1}{S^2}+\\frac{S+4}{S^2+9}\\\\\\text{Taking the inverse Laplace Transform, we have}\\\\y=x+cos3x+\\frac{4}{3}sin3x"
Comments
Leave a comment